PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF MELALUI APLIKASI CLASSPOINT PADA MATA PELAJARAN FIKIH BAB MAWĀRITS DI MTS NEGERI 4 BANTUL - Khoiriyah, Binti; Lina; Mustaqim, Ali; Utama, Mohamad Maulidin Alif (STAI Asy-Syukriyyah, 2024)
The rapid development of information technology needs to be exploited in the world of education and learning. The research aims to develop interactive learning media through Classpoint applications on fikih chapter Mawārits subjects. This research uses the research and development (R&D) methodology with the development model of Robert Maribe Branch namely analysis, design, development, implementation, and evaluation. (ADDIE). The research was conducted during the month of March until April 2024 at MTs N 4 Bantul. Subjects in this study are students of grade 9H MTs N 4 Bantul TA 2023/2024. The quality of the media developed according to the validation of the material expert was 90%. According to the media expert validation results were 95%. As for the percentage of elevation results of the teacher's response to the subject was 87.5%. The elevation result of the student response was 90.33%. Therefore, the interactive learning media through the application Classpoint on the subject fikih chap Mawārits deserves to be used in the learning process.